The Impact of Reminiscence Therapy on the Emotional Well-being of Elderly Individuals with Dementia - Rangkuti, Saddiyah; Nazwa, Liyan Aulia; Aqilla, Nasyah; Aurelia, Iriana (International Journal of Nursing and Midwifery Research, 2024)
This study examines the effectiveness of reminiscence therapy in enhancing the emotional well-being of elderly individuals diagnosed with dementia, a condition often accompanied by emotional distress, including depression and isolation. The research involved a diverse group of elderly participants at varying stages of dementia who participated in a structured reminiscence therapy program over several weeks. Data collection included pre- and post-intervention assessments using the Geriatric Depression Scale (GDS) and qualitative interviews to evaluate participants’ emotional responses. Results indicated a statistically significant reduction in depressive symptoms and improved emotional states, especially among those in the early stages of dementia. Qualitative feedback highlighted increased joy, connectedness, and a strengthened sense of identity among participants. The findings emphasize the necessity of tailoring reminiscence therapy to accommodate different cognitive abilities and advocate for a multimodal approach to enhance engagement and therapeutic outcomes. The study supports the integration of reminiscence therapy into dementia care practices, reinforcing its role in improving the quality of life for elderly individuals. Future research is encouraged to explore the long-term effects and further optimize intervention techniques to maximize the benefits of reminiscence therapy.